2014
DOI: 10.1534/genetics.114.167502
|View full text |Cite
|
Sign up to set email alerts
|

Mei-P26 Mediates Tissue-Specific Responses to the Brat Tumor Suppressor and the dMyc Proto-Oncogene inDrosophila

Abstract: TRIM-NHL proteins are a family of translational regulators that control cell growth, proliferation, and differentiation during development. Drosophila Brat and Mei-P26 TRIM-NHL proteins serve as tumor suppressors in stem cell lineages and have been proposed to exert this action, in part, via the repression of the protooncogene dMyc. Here we analyze the role of Brat, Mei-P26, and dMyc in regulating growth in Drosophila imaginal discs. As in stem cell lineages, Brat and Mei-P26 repress dMyc in epithelial cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…As members the TRIM-NHL protein family, TRIM2, TRIM3, TRIM32 and TRIM71 share structural homology in the C-terminus, which contains a filamin domain and NHL-repeat motifs [ 1 , 23 26 ]. Moreover, TRIM71 shares functional homology with other TRIM-NHL family proteins in terms of ubiquitin ligase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As members the TRIM-NHL protein family, TRIM2, TRIM3, TRIM32 and TRIM71 share structural homology in the C-terminus, which contains a filamin domain and NHL-repeat motifs [ 1 , 23 26 ]. Moreover, TRIM71 shares functional homology with other TRIM-NHL family proteins in terms of ubiquitin ligase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several groups have implicated TRIM32 in tumor formation based on studies initially performed in Drosophila melanogaster [ 1 ]. These early studies showed that mutations in brat and mei-26, ortholog of TRIM32 in the fly, cause tumor formation in Drosophila [ 23 ]. In mammalian cells, TRIM32 has been shown to modulate TNF-mediated apoptosis through ubiquitination of XIAP (X-linked inhibitor of apoptosis) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, immunoprecipitation with ovary lysates showed that Wh interacted with dMyc ( Fig. 6K), which is targeted by Mei-p26 for degradation in the wing disc (Ferreira et al, 2014). Removal of one dmyc copy from nos>wh RNAi germaria significantly rescued the number of large nucleoli present in GSCs or early germ cells (Fig.…”
Section: Wh Suppresses Nos Translation Ribosomal Biogenesis and Micrmentioning
confidence: 93%
“…This mutation strongly suppressed (α=7.3×10 −7 ) the wing phenotype showing that UY1131 is a LOF of brat (data not shown). Brat belongs to the NHL family of proteins, represses translation of specific mRNAs 38] and is a negative regulator of cell growth [39-41]. The suppression of bax -induced phenotypes by a LOF of brat could suggest that this gene also regulates cell death, which seems unlikely according to its inability to suppress other cell death pathways [37].…”
Section: Discussionmentioning
confidence: 99%